effect of Isovalent and aliovalent cation substitution on the structure and functional properties of (Mg,Co,Ni,Cu,Zn) O high entropy oxide : - Gautam, Ashwani (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Ceramic Engineering